Antibibiotics Susceptibility Testing Against Staphylococcus Aureus from Nasal Isolates in Food Handlers in Canteen of Mataram University - Suryantarini, Ni Wayan Puspa Wijaya; Hasbi, Nurmi; Ayunda, Rahmah Dara (Jurnal Biologi Tropis, 2024)
Staphylococcal food poisoning is caused by bacteria Staphylococcus aureus that contaminate food such as through transmission from the nose of the food handlers. Severe bacterial food poisoning requires appropriate antibiotic therapy. This study aims to test the susceptibility and compare the diameter of the inhibition zones of several antibiotics against S. aureus. The study is an experimental analytical consisting of sterilization of materials and antibiotics sensitivity testing using disc diffusion technique with replication. Statistical tests were carried out using the SPSS One Way ANOVA and Post Hoc Test. The result showed that S. aureus was still sensitive to four antibiotics with the average diameter for gentamicin, ciprofloxacin, clindamycin, and chloramphenicol were 17.7 mm, 28.95 mm, 23.58 mm, and 23.08 mm, respectively. Statistical tests showed a significant difference in the diameter of inhibition zone from four antibiotics (p < .05). Ciprofloxacin produced the largest inhibition zone and gentamicin produced the smallest zone, while clindamycin and chloramphenicol did not show a significant difference (p > .05). It can be concluded that the four antibiotics are still suitable to treat diseases such as food poisoning caused by S. aureus. Personal hygiene of food handlers is important to prevent transmission of disease through food. Prevention of antibiotic resistance is carried out by paying attention to the appropriate use of antibiotics in the community. Further research with the larger size of sample and other antibiotics using different techniques is needed.